2019
DOI: 10.1002/cbin.11180
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles promote osteogenic differentiation of human periodontal ligament fibroblasts by regulating the RhoA–TAZ axis

Abstract: Silver nanoparticles (AgNps) are well established antibacterial agents, which have been reported to promote osteogenesis of stem cells. Ras homolog gene family member A (RhoA) and Tafazzin (TAZ) have been recently shown to be involved in osteogenic differentiation. The present study aimed to evaluate the effects of AgNps on osteogenic differentiation of human periodontal ligament fibroblasts (HPDLFs), and investigate the underlying mechanisms of AgNps activity. 3‐(4,5‐Dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 32 publications
(36 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, RhoA‐TAZ signaling was recently found to be associated with hPDLFs osteodifferentiation. The latest study revealed that silver nanoparticles promoted osteodifferentiation of hPDLFs through regulating the RhoA‐TAZ signaling, 10 which was consistent with our discovery. We found that RhoA‐TAZ pathway promoted ALP activity, ARS activity and expression of COL1, RUNX2, ALP, and OCN, which was reduced by miR‐140 mimics, suggesting by inhibiting RhoA‐TAZ signaling pathway, miR‐140 suppressed the osteogenesis differentiation of hPDLFs.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Furthermore, RhoA‐TAZ signaling was recently found to be associated with hPDLFs osteodifferentiation. The latest study revealed that silver nanoparticles promoted osteodifferentiation of hPDLFs through regulating the RhoA‐TAZ signaling, 10 which was consistent with our discovery. We found that RhoA‐TAZ pathway promoted ALP activity, ARS activity and expression of COL1, RUNX2, ALP, and OCN, which was reduced by miR‐140 mimics, suggesting by inhibiting RhoA‐TAZ signaling pathway, miR‐140 suppressed the osteogenesis differentiation of hPDLFs.…”
Section: Discussionsupporting
confidence: 89%
“…Besides, we demonstrated that OE‐RhoA promoted ALP activity, ARS activity and expression of COL1, RUNX2, ALP, and OCN which was reduced by miR‐140 mimics, suggesting miR‐140 inhibited osteodifferentiation of hPDLFs by suppressing RhoA. RhoA‐TAZ pathway was reported to play functions in osteogenic differentiation in recent years 8–10 . Recent study demonstrated that icariin promoted proliferation and osteodifferentiation of rat adipose‐derived stem cells through stimulating the RhoA‐TAZ pathway 8 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the first 6 days, the QHMS and Ag@QHMS displayed a slightly positive influence on the proliferation of BMSCs. It is considered that the slowly released Si and Ag ions in solution may then affect the cytoskeleton through the ROCK-1 pathway mediated by β -integrin, which leads to the promotion of osteoblast division and differentiation [ 18 , 40 ]; however, the specific mechanism still needs to be further verified. After 7 days of coculture, the cell proliferation in all groups decreased, although the difference was not significant compared with the negative control group.…”
Section: Discussionmentioning
confidence: 99%